La territorialisation des politiques environnementales. Le cas de la pollution nitrique de l’eau par l'agriculture - Anne Lacroix; François Bel; Amédée Mollard; Emmanuelle Sauboua (Développement Durable et Territoires)
The paper starts with the wide variability of nonpoint water nitrogenous pollution generated by agriculture. This variability depends especially on climate, soil types and farming systems. Our interdisciplinary researches, carried out on two different sites in France, show that space and time heterogeneity influence farm practices to be implemented in order to reduce pollution at the standard level. Hence the most cost-effective farm practices are different from one place to another, depending on local characteristics. Therefore this result emphasises the potential efficiency of spatially targeted policies. Theoretically, such policies are considered optimal, since economic agents tune their efforts according to the sensitivity of the milieu where they operate. But, according to empirical analyses, this advantage is counteracted by a high cost of implementation, monitoring and enforcement. In order to maintain the advantage of site-specific policies versus uniform policies, the former have to be implemented at an optimal level of space. This level should at least allow for a trade-off between lower expenses due to an appropriate tuning to the local conditions and heavier costs of decentralised measures. This paper deals with this specific question regarding territorialized policies. It is based on a study of the efficiency of differentiating the way this pollution is regulated, focussed on assessing the importance of spatial variability in physical parameters and in site-specific policies' costs.